Development of Digital Interactive Worksheets Based on a Differentiated Instruction Model in Science Education to Enhance Scientific Literacy in Physics Among Junior High School Students - Kasmawati; Eni Sumanti Nasution; Fauziah Nasution (Jurnal Penelitian Pendidikan IPA, 2025)
The integration of technology in education is essential for enhancing learning, particularly in junior high school Science. Challenges such as low conceptual understanding and limited scientific literacy remain prevalent. This study developed a differentiation-based Digital Interactive Worksheet (DIW) to improve students’ scientific literacy in motion concepts. Using the ADDIE model within a Research and Development (R&D) framework, the study involved 30 eighth-grade students at SMP Negeri 5 Padangsidimpuan. Data were collected through expert validation sheets, practicality questionnaires, and scientific literacy tests. Results indicated that the DIW was highly valid (81.2%), practical (84.6%), and effective in enhancing students’ scientific literacy. Small-scale trials produced an N-Gain of 55.8% (moderate), while large-scale trials showed an N-Gain of 49.9% (moderate), suggesting consistent effectiveness, though slightly lower in larger classes likely due to management challenges. The 5.9% difference highlights the importance of classroom strategies for larger groups. DIW’s success is attributed to interactivity, personalized learning, real-time feedback, and active student engagement. This study contributes a tested digital learning tool for Science education and demonstrates the effective integration of differentiation and technology. The findings support SDG 4 (Quality Education) through inclusive and adaptive learning. Future research should address scalability and broader classroom implementation.